Characteristics of Fractures of the Appendicular and Axial Skeletons in Rabbits and Hares: A Retrospective Study - Rodrigues, C. S.M.P. [UNESP]; Rahal, S. C. [UNESP]; Silva, J. I.S. [UNESP]; Silva, J. P. [UNESP]; Mamprim, M. J. [UNESP]; Figueroa, J. G. [UNESP]; Tokashiki, E. Y. [UNESP]; Melchert, A. [UNESP] (My University, 2022)
BACKGROUND: The frequency and characteristics of fractures may vary according to the environment. OBJECTIVES: The present study aimed to assess the fractures of the appendicular and axial skeletons in rabbits (Oryctolagus cuniculus) and hares (Lepus sp.) presented at a veterinary teaching hospital. METHODS: Medical records and radiographs were retrospectively analyzed over eight years. RESULTS: Twenty-six pet rabbits and five free-ranging hares were enrolled in this study. Twenty-one of them had fractures in the appendicular skeleton, nine in the axial skeleton, and one in both. The fractures were related to traumatic events, such as being hit by a vehicle (22.58%), falling (12.9%), being attacked by another animal (12.9%), and having a paw stuck in a hole (3.22%); 48.38% had an unknown cause. Long bone fractures were found in the humerus (n=2), radius/ulna (n=1), femur (n=5), and tibia (n=12). Fractures involving the distal aspects of the limbs included the tarsus (n=1) and metatarsus (n=2) bones. Except for one rabbit, all of the others had unilateral fractures. Fourteen presented closed fractures, and nine were open fractures. All these fractures were complete, 56.52%% simple, and 43.47% multifragmental. The procedures used included osteosynthesis (42.85%), external coaptation (28.57%), amputation (14.28%), euthanasia (4.76%), and two animals died (9.52%). The fractures of the axial skeleton included the vertebral column (n=6), mandible (n=3), and pelvis (n=2). Five fractures were treated conservatively, and the rabbits were euthanized in four cases. CONCLUSIONS: The fractures resulted from a traumatic episode, which had an unknown origin in most of the cases, involving mainly the appendicular skeleton, being the tibia the bone most affected.
Keywords: Bone; Lagomorphs; Radiography; Trauma